HUBUNGAN PEMBERIAN NUTRISI DENGAN KEJADIAN STUNTING PADA BALITA DI KELURAHAN KARANG ANYAR - Utami, Ressa Andriyani (Jurnal Kesehatan Holistic, 2017)
Stunting is a condition where the bodyof a person is short and very short with a value of -2 standard devians deficit below the median. The purpose of this study was to determine the relationships between family characteristics and parenting nutrients stunting incident. The research was design as descriptive observational with cross sectional approach. A total sample of 192 people was involved through the cluster sampling technique. The results showed that there is a relationship between family characteristics, and parenting nutrients with the incidence of stunting in children under five. The dominant factors associated with the incidence of stunting are attitude (OR=2.290) and behavior (OR=2.185). This research is expected to provide an overview and input for the family, the community and the relevant agencies to solve the problem of stunting in children under five.